Problematika Dalam Kelompok Sosial: (Studi Kasus Penutupan Pesantren Waria Di Kotagede Yogyakarta) - Moh. Khoirul Fatih (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2018)
Yogyakarta is a name for a region in Indonesia, a region that is very unique and authentic, where the lives of its people are still thick with Javanese culture that continues to be preserved as a social identity. In addition, the pluralistic life of Yogyakarta people is an interesting concern from both cultural aspects and social interaction, one example of its uniqueness is the existence of Islamic boarding school that still exist today. The Islamic boarding school founded by the transgender group in Yogyakarta serves as a forum for friendship and coaching in terms of religious education for transgender in Yogyakarta, but in 2016 there was a conflict of plans to close the Islamic boarding school by the FJI (Islamic Jihad Front). The conflict gave birth to a responsive attitude from the social groups in transgender Islamic boarding school. The actions taken are silent and understood in this paper as symbolic interactions. This silent action was born in the minds of individuals who described his group as an attempt to resolve the conflict peacefully.